Interaction of Transportation and Location of Urban Facility Areas in the Case of the Historic Peninsula in Istanbul - Zekiye YENEN (Megaron, 2009)
The main component of accessibility in urban areas is the relation between the transportation network and land use. Improvements in technology have an effective role on the location of urban functions on behalf of urban transportation networks in addition to the economic and social life in the cities. In some cases, technological improvements in the transit systems demonstrate positive and beneficial solutions for the citizens. However, the increasing use of individual automobiles in the cities constitutes one of the most consequential difficulties. The number of automobile owners is stated to be an indicator of the advanced level of cities; however, when the rail or sea transit systems are insufficiently developed and/or when integration between the transit systems is lacking, the use of individual automobiles in daily urban travels escalates dramatically. Such a situation results in serious accessibility problems especially in the historical core of the cities, which are often not planned or developed for vehicular traffic. Under these circumstances, besides the intensive use of social and cultural activities, the speculative aims hasten the deterioration process of the historical districts and cause secondary effects in the form of noise, visual and aesthetic pollution. The Historic Peninsula in Istanbul Metropolitan Area is experiencing the above-mentioned challenges. This article puts forward the importance of the transportation network and its effects on the location of urban facility areas such as administration, education and health, which comprise the whole metropolitan area or national scale of facilities throughout the history in the Historic Peninsula. Finally, based on the hypothesis, the statistical evaluation methods of data collection and interval surveys, which were applied at sample urban facilities during the case study, were analyzed. Furthermore, the criteria for the interaction of transportation and location of urban facilities highlighted by the study are discussed. One of the striking implications is the existence of urban facility areas situated in the Historic Peninsula, which attract both metropolitan and national scale trips during the day. Today, in transportation and urban land use planning, the facilities are drawing high volumes of vehicular and pedestrian traffic out of the historic parts; however, in contrast, the Historic Peninsula is complicated and fully motorized. Furthermore, the limited building lot sizes, which cannot respond to the growing population, raises the issue of decentralization of urban facilities that also use service vehicular transportation today. These circumstances may cause Istanbul to lose the prestige of her historic center and increases the risk of the relocation of central urban facilities according to only highway access. In an effort to avert this situation, a “traffic-limited city” model is suggested for Istanbul in the final proposal section.